Recent advances in the ontogeny of drug disposition. Issue 10 (15th April 2021) - Chapron, Brian D.; Chapron, Alenka; Leeder, J. Steven
Abstract : Developmental changes that occur throughout childhood have long been known to impact drug disposition. However, pharmacokinetic studies in the paediatric population have historically been limited due to ethical concerns arising from incorporating children into clinical trials. As such, much of the early work in the field of developmental pharmacology was reliant on difficult‐to‐interpret in vitro and in vivo animal studies. Over the last 2 decades, our understanding of the mechanistic processes underlying age‐related changes in drug disposition has advanced considerably. Progress has largely been driven by technological advances in mass spectrometry‐based methods for quantifying proteins implicated in drug disposition, and in silico tools that leverage these data to predict age‐related changes in pharmacokinetics. This review summarizes our current understanding of the impact of childhood development on drug disposition, particularly focusing on research of the past 20 years, but also highlighting select examples of earlier foundational research. Equally important to the studies reviewed herein are the areas that we cannot currently describe due to the lack of research evidence; these gaps provide a map of drug disposition pathways for which developmental trends still need to be characterized.